2019
DOI: 10.1177/0960327119855128
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-promoting and migration-suppressing effect of alantolactone on gastric cancer cell lines BGC-823 and SGC-7901 via regulating p38MAPK and NF-κB pathways

Abstract: Background: Gastric cancer is a malignant tumor with high incidence rate and mortality rate. Purpose: In this study, we investigated the anti-cancer effect of alantolactone, a sesquiterpene lactone, on gastric cancer cell lines BGC-823 and SGC-7901. Methods: BGC-823 and SGC-7901 cells were treated with different concentrations of alantolactone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…alT is the main biologically active compound derived from Inula helenium (42). alT has been widely researched as a potential candidate for the treatment of several types of cancer, and previous in vivo studies have reported its antiproliferative, anti-metastatic and anti-invasive activity in a variety of cell lines (19,20,42). The present study aimed to evaluate the effect of alT on osteosarcoma and to determine whether it could be used as a potential future treatment strategy for this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…alT is the main biologically active compound derived from Inula helenium (42). alT has been widely researched as a potential candidate for the treatment of several types of cancer, and previous in vivo studies have reported its antiproliferative, anti-metastatic and anti-invasive activity in a variety of cell lines (19,20,42). The present study aimed to evaluate the effect of alT on osteosarcoma and to determine whether it could be used as a potential future treatment strategy for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that alT promotes numerous biological effects, including anti-inflammatory and antioxidant functions (18,19). it has also been observed to suppress several types of human cancer, including gastric, pancreatic and breast cancer cells (19)(20)(21). it is reported that these anticancer effects of alT are mediated through the Pi3K/aKT signaling pathway (22).…”
Section: Introductionmentioning
confidence: 99%
“…Although alantolactone is associated with allergic contact dermatitis triggered by Inula species [33][34][35], this compound was first described as anti-helminthic [36], with subsequent studies demonstrating its tremendous potential, mainly as antitumor [37][38][39][40], anti-inflammatory [26,41], and antioxidant [42] agent.…”
Section: Alantolactonementioning
confidence: 99%
“…It has different effects on different tumor cells, and even plays completely opposite effects. There was evidence demonstrating that the phosphorylation of p38 was signi cantly upregulated in gastric cancer cells when treated with alantolactone, that promoting apoptosis and mitigating migration and invasion [17]. Likewise, the p38MAPK pathway regulates the apoptosis in osteosarcoma cells [18,19] and esophageal cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%